Remotely Sensing Variation in Ecological Strategies and Plant Traits of Willows in Perialpine Floodplains. Issue 7 (13th July 2019) - Milani, G.; Kneubühler, M.; Tonolla, D.; Doering, M.; Schaepman, M. E.
Abstract: Natural floodplains are characterized by a complex habitat mosaic. However, damming, water storage, and hydropower production affect many floodplains by altering their natural habitat diversity. Field sampling data and imaging spectroscopy are used in combination with statistical models to assess resource allocation strategies of willow stands in perialpine floodplains. Three contrasting floodplain reaches located along two rivers in Switzerland serve as test beds: The Sarine River is partitioned into an upstream and downstream segment under the influence of a dam and a hydropower plant, while the Sense River represents an undisturbed, natural floodplain. Airborne imaging spectrometer data allow mapping of spatially distributed Competitor/Stress tolerator/Ruderal (CSR) strategies using a partial least square modeling approach. Using cross validation, we demonstrate that a statistical modeling approach can reveal variations in CSR scores based on the StrateFy model. Such intraspecific variation of CSR scores cannot be captured by a strategy categorization based solely on the species. Results reveal that willows shifted toward more competition and less stress tolerance along hydrologically altered reaches compared to the willows strategy along the natural control. Moreover, the overall distribution of strategies indicates that stress factors (i.e., limiting growth factors), rather than disturbance (i.e., events leading to partial or total destruction), shape the plant traits of alluvial willow trees. Detailed assessments of resource allocation strategies contribute to a more complete understanding of the continuous and reciprocal shaping between flow regimes, landforms, and alluvial vegetation. Key Points: We couple the description of plant strategies with imaging spectroscopy CSR scores based on the StrateFy model reveal variations not captured by a strategy discrimination based solely on species Plant parameter distributions indicate that stress factors, rather than disturbance, shape the plant traits of alluvial willow trees